Nutraceutical and Therapeutic Applications of Squalene - Sumi, E. S.; Anandan, R.; Rajesh, R.; Ravishankar, C. N.; Mathew, Suseela (Fishery Technology, 2018)
Squalene, an isoprenoid molecule present in large quantities in deep sea shark liver oil and in smaller amounts (0.1-0.7%) in palm, wheat-germ, olive and rice bran oils, is well known for its antilipidemic, antioxidant and membrane stabilizing properties. Squalene is a key precursor molecule in the biosynthesis of vitamins, cholesterol and steroid hormones in animals. In human, presence of this highly unsaturated hydrocarbon keeps the skin healthy and protects it from ultraviolet radiations mediated carcinogenesis. Recently, squalene has drawn major attention as high valuable compound due its potential applications in the field of pharmacological, cosmetic, and nutraceutical industries. The present review includes a brief description about the natural sources, properties and applications of squalene.